Physico-Chemical Characteristics and Analysis of Fe and Zn in Tubewell Water and Sewage Water of Bikaner City - Gupta, Suruchi; Bhatnagar, Mridula; Jain, Rashmi (Asian Journal of Chemistry, 2010)
In Bikaner, all domestic and sewage wastes are poured into Sursagar, near Junagarh Fort. This water also becomes contaminated with industrial wastes when it passes through the industrial area of Bikaner. Lastly, this waste water reaches into Vallabh Garden and Madhosingh Bari. In these regions this waste water is used for irrigation along with tubewell water. To study the impact of this polluted water on tubewell water, it was necessary to examine the physico-chemical characteristics of sewage water. For this purpose, 15 sewage water samples and 6 tubewell water samples were collected and the value of some parameters such as pH, conductivity, total dissolved solids, total hardness, alkalinity, chloride, sodium, potassium, zinc and iron, were determined. This paper presents the results of analysis of sewage water and tubewell water.